Intonation and speech nature of Sibelius musical karelika - Nilova, V.I. (Publishing House "Scientific survey", 2014)
The article is devoted to the marginal works of Jean Sibelius, the classic Finnish musician, combined total of the Karelian subjects. In analogy with the Finnish philologist Hannes Sihvo, the works of Karelian subjects in the article named as Karelika. The music karelika by Sibelius is studied not in terms of its value in the creative legacy of the composer, (which is traditional in sibeliane) but in the aspects of its role in the process of Finnish cultural and linguistic area making, as it meets the national interests of the leaders of Grand Dukedom of Finland, which was part of Russia in XIX century. The assessment of karelika by Sibelius is fundamentally new, as it represents a phenomenon in which the composer implements the creative experiment in the transition from the intonation and speech music cliches of Finland of the first half of the XIX century to the formation of speech intonation, identified by contemporaries as a Finnish national music.